How children and adolescents evaluate their families: psychometric properties and factor structure of the Evaluation of Social Systems (EVOS) scale - Grevenstein, Dennis; Schweitzer, Jochen; Aguilar-Raab, Corina (Journal of child and family studies, 2019)
The Evaluation of Social Systems (EVOS) scale was developed as a measure of the quality of social relationships vis-à-vis context-unspecific aspects of relationship quality. Although constructed for adolescents above the age of 11, it has to date only been validated in adult samples. The current study investigated if EVOS can be applied to adolescents through a cross-sectional study. We investigated factorial validity and construct validity of EVOS in a sample of adolescents with a mean age of 14.74. Additionally, we examined measurement invariance between youth and adult samples. The two-factor model that was developed for adults also held in the present study. EVOS showed good reliability and exhibited strict measurement invariance. Construct validity was supported by correlations with measures of family functioning and psychological distress. We conclude that EVOS is an economic, reliable, and valid measure of the quality of family relations in adolescents. Scores are directly comparable between youths and adults.
Published online: 19 September 2018
Gesehen am 26.07.2019